Training on Family Financial Management in Kubang Puji Villlage, Banten - Yeni Januarsi; Ina Indriana; Enok Nurhayati; Roza Mulyadi (EQUATOR SINAR AKADEMIA, 2023)
Family financial management should be done with care and a well-planned budget, as it can enhance family economic conditions and enable them to become more qualified. Households must grasp these management skills, especially housewives who are often in charge of handling family money. In Kubang Puji Village, Pontang District, we discovered the inverse phenomena. Even though many of the locals own agricultural land or are self-employed, their income has been uncertain since Covid19 hit. Furthermore, many locals struggle to manage their family's funds due to a lack of adequate financial management abilities. In this village, the